Kemunduran Benih dan Penyebabnya - Hadi Sutarno (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1984)
A seed is a reproductive unit consisting of embryo and ancillary parts that are exellently adopted to fulfill their biological functions. The successfull cultivation of useful plants largly depends on thee quality of seeds, especially its viability. The phenomenon of seed deterioration is presented. The intrinsic and extrinsic factors as the factors which influence of loss of seed vialibity are discussed. The control of seed viability during storage is interesting to study.